Effects of oregano essential oil (Origanum syriacum L.) on performance, egg quality, intestinal morphology and oxidative stress in laying hens - Gul, M.; Yilmaz, E.; Yildirim, B. A.; Sezmis, G.; Kaya, A.; Timurkaan, S.; Tekce, E. (Eugen Ulmer Gmbh Co, 2019)
This study aimed to investigate the effects that including different levels of oregano essential oil (Origanum syriacum L.) (200, 400, and 600 mg/kg) in the diets of laying hens had on performance, egg quality, and intestinal morphology, as well as egg malondialdehyde (MDA) levels, blood lipid peroxidation, and oxidative stress parameters. The study used a total of 120 Lohmann white laying hens aged 20 to 22 weeks. The experiment comprised the following three treatment groups, based on the dosages of oregano essential oil: 200 mg/kg (A), 400 mg/kg (B), 600 mg/kg (C); and a control group (K) that did not use oregano essential oil. Each group included 30 hens and each was divided into six subgroups with five hens each. In this study, feed intake and egg weight were significantly higher in the treatment groups than in the control group (P=0.046; P< 0.001). There was no difference among the groups in terms of eggshell strength, egg shape index, eggshell thickness, albumin index, or yolk index. However, there was a significant difference in eggshell weight, yolk color and Haugh unit in the experimental groups (P=0.015; P=0.031; P=0.042). The MDA levels in the yolk were lowest in group A (P< 0.05). In all groups with the exception of group A, yolk and serum MDA levels increased while superoxide dismutase, glutathione peroxidase, and catalase decreased as the doses of oregano essential oil increased (P< 0.001; P< 0.001; P< 0.01; P< 0.001). There was no significant serum glutathione level. In the histological analysis of the intestine, the villus height was higher in group C than in the control group (P=0.010). Based on these results, we concluded that 200 mg/kg was the most effective dose of oregano essential oil for improving performance, egg quality, and intestinal morphology while reducing oxidative stress in laying hens.
Einfluss von oregano-öl (Origanum syriacum l.) auf leistung, eiqualität, darmmorphologie und oxidativen stress bei legehennen
Keywords: Egg quality; intestine; laying hen; oregano; oxidative stress